Promoting public confidence in the medical profession: Learning from the case of Dr. Bawa-Garba. (March 2020) - Case, Paula; Sharma, Gunjan
In a 2015 prosecution which divided public opinion, Dr Bawa-Garba was convicted of gross negligence manslaughter and sentenced to 2-years' imprisonment, suspended for 2 years. The post-conviction litigation which sought to determine whether and when Dr Bawa-Garba could return to clinical practice threatened to destabilise the already fragile relationship between the medical profession and its regulator, the General Medical Council. At the heart of this litigation lay the regulator's quest to maintain and promote public confidence in the profession, in a case where the doctor concerned was not regarded as posing a future risk to patient safety. Using the Bawa-Garba litigation, this commentary examines the position and use of the nebulous concept of 'public confidence' within the fitness to practise framework for doctors. Although the authors' observations arise specifically from a case decided in the UK, 'public confidence' is a touchstone concept in professional regulation regimes around the world and so these observations have relevance beyond this jurisdiction. The authors argue that, for too long, use of the rhetoric of public confidence in the regulation of the medical profession has been characterised by an unsatisfactory lack of transparency, excessive deference by the courts to regulatory tribunals and that research is increasingly signalling that instinctual 'expert' judgements on the issue of 'what the public think' may be unreliable.